Unravelling interactions between active site residues and DMAP in the initial steps of prenylated flavin mononucleotide biosynthesis catalyzed by PaUbiX - Żaczek, Szymon; Dybala-Defratyka, Agnieszka (Biochimica et biophysica acta. General subjects, 2022)
Prenylated flavin mononucleotide (prFMN) is a recently discovered, heavily modified flavin compound. It is the only known cofactor that enables enzymatic 1,3-dipolar cycloaddition reactions. It is produced by enzymes from the UbiX family, from flavin mononucleotide and either dimethylallyl mono- or diphosphate. prFMN biosynthesis is currently reported to be initiated by protonation of the substrate by Glu140. Computational chemistry methods are applied herein - Constant pH MD, classical MD simulations, and QM cluster optimizations. Glu140 competes for a single proton with Lys129 prior to prFMN biosynthesis, but it is the latter that adopted a protonated state. Once the prenyl-FMN adduct is formed, Glu140 occurs in a protonated state far more often, while the occupancy of protonated Lys129 does not change. Lys129, Glu140, and Arg122 seem to play a key role in either stabilizing or protonating DMAP phosphate group within the PaUbiX active site throughout initial steps of prFMN biosynthesis. The role of Lys129 in the functioning of PaUbiX is reported for the first time. Glu140 is unlikely to act as a proton donor in prFMN biosynthesis. Instead, Lys129 and Arg122 fulfil this role. Glu140 still plays a role in contributing to hydrogen-bond network. This behavior is most likely conserved throughout the UbiX family due to the structural similarity of the active sites of those proteins. Mechanistic insights into a crucial biochemical process, the biosynthesis of prFMN, are provided. This study, although purely computational, extends and perfectly complements the knowledge obtained in classical laboratory experiments. [Display omitted] •At the enzyme – substrate complex, Lys129 shares a single proton with Glu140.•Glu140 is unlikely to act as a proton donor for DMAP in prFMN biosynthesis.•Transfer of protons to DMAP does not initiate the whole prFMN biosynthesis on its own.•Based on the QM calculations, protonation of the phosphate group takes place during the formation of the FMN-prenyl adduct.•The observed behavior is likely to be conserved within the whole UbiX enzyme family.